Distinguishing verbal Expression of feelings and felt-sense A cross – sectional study among psychology student - كاسوحة, سليمان (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to identify the level of expression of feelings and feelings among psychology students in Damascus University. And the detection of differences in verbal expression according to the variables of gender (Male-Female), the number of siblings and the school year. The researcher used a tool prepared by him after arbitration and testing its validity and reliability. The results of the research showed that the level of expression of feelings among the individuals of the research sample was medium at a rate of (61.08%), followed by a percentage of (22.16%) who had a low level of expression of feelings, while the percentage of individuals with a high level of expression of feelings was (16.76%). There are statistically significant differences between the mean scores of the research sample on the expression of emotions and feelings scale according to the gender variable, and the differences are in favor of females with the largest arithmetic mean. There are no statistically significant differences between the mean scores of the research sample on the expression of feelings and feelings scale, according to the number of siblings variable. There are differences between the arithmetic mean scores of the respondents on the total score of the scale according to the variable of the academic year between: * Students of the fourth and fifth years and students of the years (first, second and third) in favor of the students of the fourth and fifth years.